The Relationship Between Nurses Spiritual Support and the Anxiety Levels of Preoperative Patients with Closed Fractures at Meuraxa Hospital, Banda Aceh - Hasniah Hasniah; Siti Hamidah; Munazar Munazar (Lembaga Teewan Journal Solutions, 2026)
Surgery or operations are all medical procedures using invasive procedures, with the stages of opening or exposing the part of the body being treated. Surgery is performed to diagnose or treat an illness, disability or injury, as well as treat conditions that cannot be cured with simple procedures or medication (Poter, P.A. Perry. 2016). This surgery can be caused by various things, including bone fractures ( fracture). A fracture is a break in the continuity of bone tissue caused by force or external pressure that is greater than the bone can absorb. Fractures experienced will have an impact on psychological and social problems. One of the problems that arises is anxiety. The aim of this research is to determine the relationship between nurse assistance and spiritual services: Prayer and Tawakkal on the anxiety level of pre-closed fracture surgery patients at Meuraxa Hospital, Banda Aceh City. Research method The research design used is analytical with a Cross Sectional Study approach. The number of samples in this study was 43 respondents. The sampling technique used was accidental sampling. The research was carried out on 06 April-01 May 2021. The results showed that of the 43 respondents in the surgical room, men and women received good assistance, 2 people (4.7%), 14 people (32.6%) received adequate assistance and less assistance. as many as 27 people (62.8%), of the 43 respondents in the surgical ward, men and women experienced mild anxiety as many as 7 people (16.3%), moderate anxiety as many as 15 people (34.9%), severe anxiety as many as 21 people (48.8%). and the results of bivariate analysis show P value = 0.032 <0.05 which states that there is a relationship between nurse assistance and spiritual services: Prayer and Tawakkal on the anxiety level of pre-closed fracture surgery patients at Meuraxa Hospital, Banda Aceh City in 2021. Conclusion: there is a relationship Accompanying nurses with spiritual services: Prayer and Tawakkal with the anxiety level of pre-closed fracture surgery patients at Meuraxa Hospital, Banda Aceh City in 2021.